KESEJAHTERAAN KELUARGA NELAYAN DI KENAGARIAN PASAR LAMA MUARA AIR HAJI KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Mardini Rifenza; Deded chandra (JURNAL BUANA, 2020)
This study was intended to provide a welfare for the fishermens family in Nagari Pasar Lama Muara Air Haji sub-district Linggo Sari Baganti regency Pesisir Selatan,. This type of research uses a quantitative descriptive method. Data retrieval technique is a propotional random sampling of 35 respondenrs. The data processing equipment used is numerals and data processing using percentages and using the likert scala surveyors (Sugiyono:2010). The sesult of the study is food average score of 2,9 is a moderate category, the average clothing of a 3,2 is in the category score average,the average shelter was 2,4 in the lowcategory,the average education score was 3,1 in the hihg, health average score 3,4 is in the high category and income Rp 1.500.000-Rp1.000.000/month. Keywords : fisherman, food, clothing shelter, education, health and income